PERLAWANAN TOKOH PEREMPUAN DALAM NASKAH DRAMA RINA NAZARUDDIN ‘SENANDUNG DAYANG DERMA’ - Suci Ayu Latifah; Hetty Purnamasari; Sutejo - (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2022)
ABSTRACT The purpose of this study is to describe the forms of resistance of female characters in the drama script Senandung Dayang Derma by Rina Nazaruddin. The script tells the struggle of Dayang Derma's character to get freedom of speech over the slander that befell her lover Awang Mahmuda. Awang Mahmuda has been slandered to steal his stepfather's money so that his name is bad, and finally left the house. The slander was carried out by Awang Mahbungsu to get Dayang Derma as a prospective wife. Finally, the truth was revealed and Dayang Derma kept promising to hum the truth. Qualitative descriptive literature is the research method used, while literature study and content analysis are data analysis techniques. Borrowing the existentialist feminism theory of Simone de Beauvoir, the resistance of female characters is examined. Existentialist feminism is a study that reveals the efforts and efforts of women's movements in demanding gender equality with men. This movement removes the negative stigma of women who are weak, fragile, and only focus on household matters. The findings show that there are forms of resistance, such as freedom of ideology, courage to demand rights, and fighting negative stigma.